2005
DOI: 10.1021/bc049707r
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cell Attachment to a Biomimetic Polymer Surface through the Recognition of Cell-Surface Tags

Abstract: Reactive phosphorylcholine polymers, which can recognize biosynthetic cell-surface tags, were synthesized to control cell attachment. Human promyelocytic leukemia cells (HL-60) with unnatural carbohydrates as cell-surface tags were harvested by treatment with N-levulinoylmannosamine (ManLev). The attachment of ManLev-treated HL-60 cells to 2-methacryloyloxyethyl phosphorylcholine (MPC) polymers with hydrazide groups was studied. HL-60 cells, which are nonadhesive, did not attach to any polymer surface without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…PDL cells hardly adhered and proliferated on PMPC, which was consistent with the findings of a previous study by Iwasaki et al, who reported that adhesion of human promyelocytic leukemia cells and human uterine cervical cancer cells was completely suppressed on PMPC [36]. We previously reported that, we previously reported that PMEA has excellent biocompatibility with human blood cells [15].…”
Section: Resultssupporting
confidence: 90%
“…PDL cells hardly adhered and proliferated on PMPC, which was consistent with the findings of a previous study by Iwasaki et al, who reported that adhesion of human promyelocytic leukemia cells and human uterine cervical cancer cells was completely suppressed on PMPC [36]. We previously reported that, we previously reported that PMEA has excellent biocompatibility with human blood cells [15].…”
Section: Resultssupporting
confidence: 90%
“…Some investigators have sought to take advantage of the properties of HA by combining HA with other biomaterials, including collagen [23,24], gelatin [25][26][27] and chitosan [28][29][30], to produce scaffolds or membranes used for tissue engineering. In this study, we hypothesized that HA could provide superior effects on the formation, structural and biological properties of fibroin-based scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…In other cases, direct chemoselective ligation of fluorescent molecules [49,56] or contrast agents [57] has been reported. Probes have also included therapeutic agents such as toxic proteins [50] and small-molecule drugs [58], additional sugar epitopes [51], quantum dots [54], adenoviruses used for gene delivery [59], as well as polymers [60] and functionalized materials intended to facilitate cell adhesion and serve as a growth substrate [54,61].…”
Section: Metabolically Engineered Glycans Alter the Chemical Propertimentioning
confidence: 99%
“…In a second example of using exogenous precursors to influence bacterial carbohydrate biosynthesis, the Nishimura laboratory synthesized UDP-MurNAc pentapeptide derivatives that were metabolically incorporated into cell-wall components of Lactobacilli plantarum [103], thereby changing the adhesive properties of these bacteria [104]. Both strategies offer a way to identify the pathogen to the immune system for eradication, or to adhesive constructs for removal from the body [60,61].…”
Section: Pathogens and Infectious Agentsmentioning
confidence: 99%
See 1 more Smart Citation